Adolescent Health Literacy and Neighbourhood Features: HBSC Findings from Czech Republic, Poland, and Slovakia - Kleszczewska, Dorota; Porwit, Katarzyna; Boberova, Zuzana; Sigmund, Eric; Vasickova, Jana; Paakkari, Leena (International journal of environmental research and public health, 2021)
The role of supportive environments on health, wellbeing, and longevity has been widely recognized. However, there is no strong empirical evidence on the association between health literacy (HL) as a particular health-related competence and neighbourhoods. Therefore, the aim of the study was to assess the association between the features of neighbourhoods and the level of HL competencies of young people from three countries (Czech Republic, Poland, Slovakia). Self-reported data from an international sample of 11,521 students aged 13-15 years participating in the Health Behaviour in School-aged Children Study (HBSC) in the year 2018 were included in the analyses. The level of HL shows a strong positive relationship with family wealth, and a significant relationship is maintained in all studied countries. Both social and structural features of neighbourhoods turned out to have an impact on students' HL. However, HL is most clearly explained by the school environment. This study confirms the school effect on higher levels of HL competences in adolescents. This indicates the need to invest in schools located in less affluent areas to generally improve the level of education, implement modern health education combined with HL, and strengthen the social and health competencies of students.
Keywords: adolescents; Humans; dítě; Child; Schools; Polsko; neighbourhood; lidé; Poland; zdravotní gramotnost; Health Literacy; Slovenská republika; Slovakia; zdraví dospívajících; školy; Adolescent Health; Adolescent; Czech Republic; Česká republika; health literacy; mladiství